The Concept of Education in the Family, School, and Society within the Framework of Value and Character Education - Nurlela Salim (Pinisi Journal of Social Science, 2023)
Value and character education plays an important role in the formation of individuals with ethics and integrity. This education is not only limited to the school environment, but also involves families and communities as partners in building positive values and character in the younger generation. This study aims to analyze the concept of value and character education in the context of family, school, and community. In the education of values and character in the family, the role of parents is very important. They model and teach moral values to their children through daily interactions. Open communication and a loving approach in the family are important foundations in forming good character. In schools, teachers have a great responsibility in developing values and character in students. A structured character education program can be implemented in the curriculum to help students understand values such as honesty, discipline, responsibility, and empathy. Schools can also create an environment that supports character building by involving students in social activities and supporting the development of positive attitudes. Society also plays a role in value and character education. Non-governmental organizations, religious institutions, and local communities can provide support and extend values and character education beyond the school environment. Collaboration between families, schools, and communities is needed to ensure continuity of value and character education across multiple contexts of children's lives.